Standar Mutu Pengelolaan Madrasah Perspektif Filsafat Pendidikan Islam - Subakri Subakri (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2020)
This article discusses the quality standard of madrasah management perspective of Islamic education philosophy. From the results of the study, it can be concluded that the criteria for measuring success in prioritizing madrasah management on quality, namely: the number of students receiving services is increasing; the level of classroom living is declining, and school productivity is getting better; the relevance of better education; increased stakeholder involvement; teacher and school staff welfare improved, and democratization in the administration of education. The basis for managing quality-based management in the study of Islamic Education philosophy is: doing work with itqan (precise, clear, and directed); reach the goal earnestly; management concept. Keywords; Quality Standards, Management, Madrasah, Philosophy Of Islamic Education.